A novel task to evaluate irony comprehension and its essential elements in Spanish speakers - Valles-Capetillo, Elizabeth; Ibarra, Cristian; Martinez, Domingo; Giordano, Magda (Frontiers in Psychology, 2022)
An ironic statement transmits the opposite meaning to its literal counterpart and is one of the most complex communicative acts. Thus, it has been proposed to be a good indicator of social communication ability. Prosody and facial expression are two crucial paralinguistic cues that can facilitate the understanding of ironic statements. The primary aim of this study was to create and evaluate a task of irony identification that could be used in neuroimaging studies. We independently evaluated three cues, contextual discrepancy, prosody and facial expression, and selected the best cue that would lead participants in fMRI studies to identify a stimulus as ironic in a reliable way. This process included the design, selection, and comparison of the three cues, all of which have been previously associated with irony detection. The secondary aim was to correlate irony comprehension with specific cognitive functions. Results showed that psycholinguistic properties could differentiate irony from other communicative acts. The contextual discrepancy, prosody, and facial expression were relevant cues that helped detect ironic statements; with contextual discrepancy being the cue that produced the highest classification accuracy and classification time. This task can be used successfully to test irony comprehension in Spanish speakers using the cue of interest. The correlation of irony comprehension with cognitive functions did not yield consistent results. A more heterogeneous sample of participants and a broader battery of tests may be needed to find reliable cognitive correlates of irony comprehension.